Influence of Childhood Maltreatment, Adulthood Stressful Life Events, and Affective Temperaments on Premenstrual Mental Symptoms of Nonclinical Adult Volunteers - Wakatsuki Y (Dove Medical Press, 2020)
Yumi Wakatsuki,1 Takeshi Inoue,2 Naoki Hashimoto,1 Yota Fujimura,2 Jiro Masuya,2 Masahiko Ichiki,2 Hajime Tanabe,3 Ichiro Kusumi1 1Department of Psychiatry, Hokkaido University Graduate School of Medicine, Sapporo 060-8638, Japan; 2Department of Psychiatry, Tokyo Medical University, Tokyo 160-0023, Japan; 3Department of Clinical Human Sciences, Graduate School of Humanities and Social Sciences, Shizuoka University, Shizuoka 422-8529, JapanCorrespondence: Takeshi InoueDepartment of Psychiatry, Tokyo Medical University, 6-7-1 Nishishinjuku, Shinjuku-ku, Tokyo 160-0023, JapanTel +81-3-3342-6111Fax +81-3-3340-4499Email tinoue@tokyo-med.ac.jpBackground: Previous studies have shown that childhood maltreatment is associated with premenstrual dysphoric disorder (PMDD). In this study we analyzed how multiple factors, such as childhood maltreatment, affective temperaments, and adult life events influence the severity of premenstrual mental (PMM) symptoms in nonclinical adult volunteers from the community.Methods: A total of 204 participants were recruited and administered the following self-administered questionnaire surveys: PMDD scale, visual analogue scale, Patient Health Questionnaire-9, Life Experience Survey, Temperament Evaluation of Memphis, Pisa, Paris, and San Diego autoquestionnaire version, and the Child Abuse and Trauma scale. In addition to single and multiple regression analyses, structural equation modeling was used for the statistical analyses.Results: A history of neglect indirectly predicted PMM symptoms through affective temperaments in nonclinical adult volunteers. Three affective temperaments (irritable, cyclothymic, and anxious) directly predicted PMM symptoms.Conclusion: This study is the first to report that childhood maltreatment, particularly neglect, indirectly predicted PMM symptoms through affective temperaments. The results of our study suggest that affective temperament is a mediator of the influence of childhood maltreatment on PMM symptoms.Keywords: premenstrual mental symptoms, neglect, childhood maltreatment, affective temperament, TEMPS-A, structural equation modeling